You will need

- Know the angles of a triangle and at least one of its sides.

Instruction

1

Method 1. Out of the theorem of sines of a triangle. The theorem of sines States that: the sides of the triangle are proportional to the sines of the opposite angles (Fig. 1)

From this formula implies the following equality:a = 2Rsinα,b = 2Rsinβ

From this formula implies the following equality:a = 2Rsinα,b = 2Rsinβ

2

Method 2. Out of the cosines of the triangle. According to this theorem, for any plane triangle with sides a, b, c and angle α, which lies opposite the side, true equality in Fig. 2

Hence, there is a consequence:a = b/2cosα;

Also from the theorem of cosines, there is 1 more result:

b = 2a*sin(β/2)

Hence, there is a consequence:a = b/2cosα;

Also from the theorem of cosines, there is 1 more result:

b = 2a*sin(β/2)